Upaya Peningkatan Pelayanan Kesehatan (BPJS) Di Masa Pandemi Berbasis IT - Khoironi, Fajar; Ardianto, Wisnu; Sinambella, Rossa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
This pandemic demands both the government and society to adopt new working patterns. One of them is health services for the people, namely BPJS. This highly mandatory program makes work and administrative systems inevitably changed during a pandemic. One of the programs that must be changed is how to create security and comfort in carrying out administrative activities for the community to prevent the spread of Covid-19 from spreading. This service is effective and based on Government Regulation no. 20 of 2020 concerning large-scale social restrictions in order to accelerate the handling of COVID-19. In its implementation there will definitely be challenges and obstacles occurring. These problems must be resolved immediately in order to create effective and efficient services. The conclusion of this paper is to assess the extent of the effectiveness and efficiency of the program's performance. It is hoped that the use of online applications and programs to the public in addition to reducing the risk of transmission, and avoiding crowds, can also directly support the acceleration of information and technology in this digital era.